A new multilevel solar panel system for urban areas - Zenan, Ahmed Hosne; Ahmed, Sanjana; Rhaman, Md. Khalilur; Rahman, Mosaddequr Abdur (© 2013 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 39th IEEE Photovoltaic Specialists Conference, PVSC 2013; Tampa, FL; United States; 16 June 2013 through 21 June 2013 [© 2013 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/PVSC.2013.6744435. The Journal's website is at: http://ieeexplore.ieee.org/document/6744435/